STEM teacher preparation and practice for the 21st century : research-based insights - Jenlink, Patrick M. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"STEM Teacher Preparation and Practice for the 21st Century: Research-based Insights introduces the reader to a collection of thoughtful, research-based works by authors that represent current thinking about the future of science, technology, engineering, and mathematics or STEM as it known today, as well as STEM education for a rapidly evolving global society and the preparation of STEM teachers to meet the educational needs of a changing educational landscape. Each chapter focuses on STEM teaching and the preparation of teachers who will enter classrooms to instruct the next generation of students in STEM. Research in the learning sciences focuses on the cognitive, epistemological, and socio-cultural characteristics of scientific and engineering research communities in their efforts to improve Science, Technology, Engineering, and Mathematics (STEM) education. STEM education is a means to help individuals develop different strategies in order to solve interdisciplinary problems and gain skills and knowledge as they are engaged with STEM related activities through formal and informal learning programs. Research also suggests that STEM may well stand as the new general education for the 21st century. In much of the current discourse on teacher quality and preparation, two essential points for consideration have emerged: the strength of the relationship between teacher content knowledge and student achievement, and the specific representations of knowledge that are most conducive to effective teaching. Add to these two points one additional: the nature of transforming a chaotic system of discreet preparation and clinical experiences into a coherent, aligned and logical system of continuous and progressive development and support throughout a teacher's career. These three points apply to STEM teacher preparation, induction and professional learning as well as to teacher preparation, induction and professional learning in general. Importantly, the contributing authors to this book have brought to the foreground research-based insights concerning STEM teacher preparation. Each chapter presents clear paths to understanding and reimagining STEM teaching and the importance of STEM teacher preparation, acknowledging the value of STEM literacy and the interdisciplinary nature of STEM teaching"--